BIOMASSA DAN KARBON TUMBUHAN BAWAH SEKITAR DANAU TAMBING PADA KAWASAN TAMAN NASIONAL LORE LINDU - Ariani Ariani; Arief Sudhartono; Abdul Wahid (Universitas Tadulako, 2014)
Generally, at the growth phase of the forest, plants, for example ground plant can absorb CO2more higher than climax forest. This study was aimed to determine biomass and ground plants carbon around Tambing lake. Research was carried out in Tambing lake, Lore Lindu National Park area, from August through October 2013. Quantifying biomass was done by destructive method by collecting all ground plant samples in plots. Ten plots (1m x 1m) were established in south, east, north, and west part of the lake with distance between the plot is 10 m. The results showed that the biomass average were 0.26 ton ha-1, 0.48 ton ha-1, 1.12 ton ha-1and 0.93 ton ha-1 in south, east, north and west part of the Tambing lake, respectively. Hence, the average number of carbon were 0.12 ton ha-1, 0.22 ton ha-1, 0.52 ton ha-1 and 0.44 ton ha-1 in south, east, north and west part of the Tambing lake, respectively. Keywords: Biomass, Carbon, Ground plants, Tambing lake, Lore Lindu National Park.